2022
DOI: 10.3389/fbioe.2022.995266
|View full text |Cite
|
Sign up to set email alerts
|

PCL strut-like scaffolds appear superior to gyroid in terms of bone regeneration within a long bone large defect: An in silico study

Abstract: The treatment of large bone defects represents a major clinical challenge. 3D printed scaffolds appear as a promising strategy to support bone defect regeneration. The 3D design of such scaffolds impacts the healing path and thus defect regeneration potential. Among others, scaffold architecture has been shown to influence the healing outcome. Gyroid architecture, characterized by a zero mean surface curvature, has been discussed as a promising scaffold design for bone regeneration. However, whether gyroid sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 79 publications
1
13
0
Order By: Relevance
“…Using an in silico modeling approach, Jaber et al. [ 70 ] recently compared the gyroid and cubic (called strut‐like in their study) scaffold architectures to predict bone formation in the defect, taking into account the influence of mechanical cues and cellular dynamics. Interestingly, they found that the large surface curvatures of the gyroid scaffold resulted in slower tissue formation dynamics and significantly reduced bone regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Using an in silico modeling approach, Jaber et al. [ 70 ] recently compared the gyroid and cubic (called strut‐like in their study) scaffold architectures to predict bone formation in the defect, taking into account the influence of mechanical cues and cellular dynamics. Interestingly, they found that the large surface curvatures of the gyroid scaffold resulted in slower tissue formation dynamics and significantly reduced bone regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these data have clinical significance and suggest that establishing a database in which patterns of bone growth in midfacial/periorbital clinical injuries could be observed might be a crucial step in geometric design of tissue-engineered scaffolds to maximize bone regeneration. Many in silico studies, [26][27][28] which resort to radiological or histological data from longitudinal pre-clinical studies to computationally simulate bone regeneration, can significantly benefit from these findings to streamline and enhance their models.…”
Section: Discussionmentioning
confidence: 99%
“…The presented micro-MPA model closely approximates the tissue continuum with resolution of 10.5 μm. Prior state-of-art reported a resolution of 10 μm for their agent-based models ( OReilly et al, 2016 ; Jaber et al, 2022 ). Thus, the micro-scale resolution of the micro-MPA model contributes to the effort of approximating the intricate spatial dynamics involved in bone regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue resorption was not reported in the study, nor were there any considerable resorption volumes identifiable from the results ( Borgiani et al, 2021 ). In contrast, Jaber et al (2022) reported the relative bone resorption signal predicted from the applied mechanical loading and successfully demonstrated resorption of volumes of bone experiencing low strain. Unfortunately, the maximum theoretical bone resorption rate (BRR 0.17%/day) predicted by the applied mechanical loading was not representative of in vivo BRR observed via micro-computed tomography (micro-CT) during the final bone remodelling phase of bone regeneration (0.52% ± 0.25%/day) ( Wehrle et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%